2005
DOI: 10.1002/chem.200500116
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Raman and UV‐visible‐NIR Spectroscopy on the Preparation of Supported Catalyst Bodies: Controlling the Formation of H2PMo11CoO405− Inside Al2O3 Pellets During Impregnation

Abstract: The physicochemical processes that occur during the preparation of CoMo–Al2O3 hydrodesulfurization catalyst bodies have been investigated. To this end, the distribution of Mo and Co complexes, after impregnation of γ‐Al2O3 pellets with different CoMoP solutions (i.e., solutions containing Co, Mo, and phosphate), was monitored by Raman and UV‐visible‐NIR microspectroscopy. From the speciation of the different complexes over the catalyst bodies, insight was obtained into the interaction of the different componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
95
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 112 publications
2
95
0
3
Order By: Relevance
“…To-date, a number of microscopic methods, such as IR, UV/Vis, Raman, and interference microscopy have been applied to study various steps in catalyst preparation and diffusion of organic compounds in the microporous materials. [7][8][9][10][11] Recently, two in-situ microspectroscopic techniques have been developed independently; these techniques allow us to study electrophilic substitution reactions in H-ZSM-5 crystals of micrometer dimensions in a space-and time-resolved manner. The first approach involves the use of an inverted confocal fluorescence microscope, as pioneered by Roef-A C H T U N G T R E N N U N G faers et al, [12,13] to investigate the alkylation of anisole and the self-condensation of furfuryl alcohol at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…To-date, a number of microscopic methods, such as IR, UV/Vis, Raman, and interference microscopy have been applied to study various steps in catalyst preparation and diffusion of organic compounds in the microporous materials. [7][8][9][10][11] Recently, two in-situ microspectroscopic techniques have been developed independently; these techniques allow us to study electrophilic substitution reactions in H-ZSM-5 crystals of micrometer dimensions in a space-and time-resolved manner. The first approach involves the use of an inverted confocal fluorescence microscope, as pioneered by Roef-A C H T U N G T R E N N U N G faers et al, [12,13] to investigate the alkylation of anisole and the self-condensation of furfuryl alcohol at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] The possibility to monitor the transport of different components inside catalyst bodies in a noninvasive manner was previously illustrated in a study in which the distribution of phosphate and Pt complexes was determined in a direct manner with a multinuclear (e.g., 31 P and 195 Pt) MRI technique. [17] Recently, we briefly reported how the distribution of paramagnetic [CoA C H T U N G T R E N N U N G (H 2 O) 6 ] 2 + complexes after impregnation of support bodies can be monitored quantitatively in a noninvasive manner via their destructive effect on the 1 H NMR signal of the water solvent in MRI measurements.…”
Section: Introductionmentioning
confidence: 99%
“…3. and/or on cpordinatively unsaturated Al + -sites on the A1 2 O 3 surface at low pH [16]. A disintegration of the heteropolyanion and the formation of H x Mo 7 [8]. After impregnation with this solution, a slow transport of Mocomplexes is again observed as the O-Mo 6+ charge transfer band is absent in spectra recorded near the center of the pellet, 15 min after impregnation.…”
Section: Resultsmentioning
confidence: 96%
“…From an extensive spectroscopie study on the speciation of complexes in CoMoP-solutions, it was found that 90% of all Mo present in the CoMoP(O.l) solution is contained in a H 2 PMo,,CoO 40 " heteropolyanion [8]. This specific complex is stable in acidic CoMo-solutions at P:Mo ratios between 0.05 and 0.2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation